Strategy for Micro, Small and Medium Enterprises (UMKM) in Processing Salted Fish as Souvenirs in Meulaboh City - Rafiqah, Cut Nurul (Catalist Indo Publisher, 2025)
Background Salted fish processing business is one of the main livelihoods of the people in West Aceh Regency, especially in Meulaboh City. Based on data from the Aceh Cooperatives and SMEs Service, there are 5,332 MSME actors in West Aceh Regency, with one of the fairly developed business sectors being salted fish processing. However, the development of UMKM strategies in this sector still needs to be improved in order to compete and develop more optimally. Methods This study uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The informants in this study were five UMKM actors in salted fish processing in Meulaboh City. Data analysis was carried out using qualitative data analysis techniques. Results The results of the study indicate that the strategy of MSMEs in processing salted fish as souvenirs in Meulaboh City is still not optimal. In terms of processing technology, MSMEs still rely on human labor without the use of modern technology. However, in marketing strategies, MSMEs have utilized social media such as Facebook and Instagram, although their use has not been maximized. The innovation strategies implemented include the use of special drying equipment based on the natural convection system and packaging salted fish in plastic containers tied with rubber or plastic ropes to prevent contamination by dust and flies. Meanwhile, in the operational strategy, MSMEs strive to maintain product cleanliness and quality by choosing fresh fish as the main raw material. Conclusions Thus, although there are several digital innovation and marketing efforts, the strategy of salted fish processing MSMEs in Meulaboh City needs to be improved, especially in the application of processing technology and development of marketing strategies in order to increase competitiveness and business sustainability.